Epitope-based peptide antigen of pepper yellow leaf curl Thailand virus for specific antibody production - Pumrachat, S.; Hongprayoon, R. (International Journal of Agricultural Technology, 2021)
Yellow leaf curl disease (YLCD) is one of the most devastating diseases causing significant yield loss to economic crops, especially peppers in Thailand. One of the reported causal agent is pepper yellow leaf curl Thailand virus (PepYLCTHV) which belongs to Begomovirus, Geminiviridae. Anti-PepYLCTHV antibody using peptide conjugate antigen was produced in this research. The peptide sequence was based on the virus coat protein sequences available in the GenBank database. Linear epitope sequences were analyzed using the IEDB program and compared to known, three-dimensional structures of African cassava mosaic virus. The synthesized peptide was conjugated with bovine serum albumin (BSA) and ovalbumin (OVA). Peptide-BSA conjugate was immunized into a New Zealand White rabbit with complete adjuvant in the first week and with incomplete adjuvant in the third week. The antiserum was collected for 12 weeks and the highest titer at 409,600, determined by indirect plate-trapped antigen enzyme-linked immunosorbent assay, was obtained. Characterization of the produced antibody showed specificity to PepYLCTHV and one more begomovirus, tomato leaf curl New Delhi virus, without cross reaction with 31 other viruses tested. Although the antibody had limited sensitivity, development of serological techniques using this antibody demonstrated good results for dot immunobinding assay and tissue print-immunoblotting. This is the first report of antibody production for PepYLCTHV using peptide antigen which can be further applied for virus detection